Minimal pronouns, logophoricity and long‐distance reflexivisation in Avar1. (April 2017) - Rudnev, Pavel
Abstract: This paper discusses two morphologically related anaphoric pronouns in Avar (Avar‐Andic, Nakh‐Daghestanian) and proposes that one of them should be treated as a minimal pronoun that receives its interpretation from a λ ‐operator situated on a phasal head whereas the other is a logophoric pronoun denoting the author of the reported event.